Transnational organised crime : perspectives on global security - Edwards, Adam, 1968-; Gill, Peter, 1947- (Transnational crime., 2003)
Considers the origins of transnational organised crime, how it has been defined and measured, governments' policy responses and its place on the policy agendas of the UN and EU in the wake of the 'war on terror'.